PENDIDIKAN MULTIKULTURAL DI PONDOK PESANTREN SYI’AH (STUDI KASUS DI PONDOK PESANTREN DARUT TAQRIB JEPARA) - Ahmad Saefudin; Fathur Rohman (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2018)
Shi’ah as a minority sect in Islam tends to be perceived negatively by majority group. However, sign of enmity between Sunnis and Shiites are never seen in Jepara. As one of the territory in Indonesia, Jepara is different from other areas that have been attacked by conflicts such as Sampang, Bangil, or Pekalongan. Sunni-Syhiites harmony in Jepara is certaintly not separated from the important role of da'wah and Islamic education conducted by Darut Taqrib Islamic Boarding School, Krapyak Jepara. This research intends to deepen the multicultural education practices conducted by the minority of Shiites in Jepara by taking the background in Shiites Boarding School Darut Taqrib. As the only institution of Shiite boarding school, Darut Taqrib always instills tolerance and multicultural values. Research data collection uses qualitative descriptive method with case study approach. The researcher attempt to collect data on the content of multicultural education, take the meaning, and understand it. The result of data analysis indicates that the existing multicultural education practice in Darut Taqrib are three kinds, open forum of tabayyun, harmonization of inclusive social interaction, and fostering of nationalism spirit among students.